Nephrogenic Syndrome of Inappropriate Antidiuresis Mimicking Hyporeninemic Hypoaldosteronism: Case Report of Two Infants - Jamala Mammadova; Cengiz Kara; Eda Çelebi Bitkin; Elif İzci Güllü; Murat Aydın (JCRPE, 2023)
Nephrogenic syndrome of inappropriate antidiuresis (NSIAD) is an X-linked disease caused by activating mutations in the arginine vasopressin (AVP) receptor-2 (AVPR2) gene. Affected patients excrete concentrated urine despite very low levels of AVP, and consequently develop euvolemic hyponatremia. Due to its low frequency, patients may be misdiagnosed and treated incorrectly. We report two related male infants with NSIAD that was initially confused with hyporeninemic hypoaldosteronism (HH). First, a 2-month-old male presented with hyponatremia, low plasma osmolality, relatively high urine osmolality, and low plasma renin-aldosterone levels. These clinical and laboratory findings were compatible with syndrome of inappropriate antidiuretic hormone (ADH) secretion without apparent cause. Consequently, fludrocortisone was initiated with a presumptive diagnosis of HH. While correcting hyponatremia, fludrocortisone treatment led to hypertension and was discontinued promptly. The second patient, aged one year, was admitted with a history of oligohydramnios, had been hospitalized four times due to hyponatremia since birth, and had a diagnosis of epilepsy. Similarly, the second infant had clinical and laboratory findings compatible with syndrome of inappropriate ADH secretion with no apparent cause. Fluid restriction normalized his serum sodium despite the plasma AVP level being undetectable. In both infants, AVPR2 gene analysis revealed a known mutation (c.409C>T; p.R137C) and confirmed the diagnosis of NSIAD. In conclusion, NSIAD should be considered in all patients with unexplained euvolemic hyponatremia despite high urine osmolality. If NSAID is not considered, the plasma reninaldosterone profile can be confused with HH, especially in infants.